Distance Education becomes Moral Distancing in UNAM’s SUAyED. Towards a Gender approach - Elenes, Evelyn (IJRDO- Journal of Educational Research, 2017)
This dissertation problematizes the conventional arithmetic measurement as aspecific resource to explain the studies of abandonment in the Distance EducationSystem of the UNAM, for which it offers a theoretical concept to be able to explainthe Psychosocial situation attitude of abandonment, namely moral distancing. Theconcept is explained dialectically through two monographs, seen from a genderperspective, of students with a failed trajectory in the system. The possibility is leftopen to solve the problem.